Heteroepitaxial growth of Pt and Au thin films on MgO single crystals by bias-assisted sputtering - Tolstova, Yulia (Sci Rep, 2016)
The crystallographic orientation of a metal affects its surface energy and structure, and has profound implications for surface chemical reactions and interface engineering, which are important in areas ranging from optoelectronic device fabrication to catalysis. However, it can be very difficult and expensive to manufacture, orient, and cut single crystal metals along different crystallographic orientations, especially in the case of precious metals. One approach is to grow thin metal films epitaxially on dielectric substrates. In this work, we report on growth of Pt and Au films on MgO single crystal substrates of (100) and (110) surface orientation for use as epitaxial templates for thin film photovoltaic devices. We develop bias-assisted sputtering for deposition of oriented Pt and Au films with sub-nanometer roughness. We show that biasing the substrate decreases the substrate temperature necessary to achieve epitaxial orientation, with temperature reduction from 600 to 350 °C for Au, and from 750 to 550 °C for Pt, without use of transition metal seed layers. In addition, this temperature can be further reduced by reducing the growth rate. Biased deposition with varying substrate bias power and working pressure also enables control of the film morphology and surface roughness.